Potential Substitution of Plantain Peel (Musa paradisiaca var. Raja) Waste Flour for High-Fiber Crispy Brownies - Theodorus Aryo Bimo Susanto; Miryam Rachel; Benediktus Yudo Leksono (Soegijapranata Catholic University, 2025)
Plantain peel (Musa paradisiaca var. Raja) is a high-fiber by-product, containing 50.3% fiber, with 16.54% pectin as a prebiotic. Plantain peel utilization is a response to 13 million tons produced annually, which contributes to environmental issues. Utilization of plantain peel in crispy brownies production offers a potential solution as ingredients with health benefits. Additionally, chicken eggshell from the previous steps were incorporated to reduce food by-product. The aim of this study is to identify the utilization of plantain peel and chicken eggshell for crispy brownies production as a functional food. The research was conducted using a systematic literature review based on research articles from 2015 until 2025 from digital base research articles, regarding the potential of plantain peel and eggshell in crispy brownies production. The addition of plantain peel has multiple health benefit like prebiotic, improvement of SCFAs production, and high phenolic components with antioxidant activity. The utilization of chicken eggshell is not just enchancing the calcium concentration in crispy brownies, which can improve teeth, bone and immune system, but also supporting the circular economy concept. The application of plantain peel and chicken eggshell utilization supports the sensory properties to crispy brownies.